2021
DOI: 10.1007/s00403-021-02276-1
|View full text |Cite
|
Sign up to set email alerts
|

Atopic dermatitis is not associated with SARS-CoV-2 outcomes

Abstract: Atopic dermatitis is characterized by immune dysregulation, which may predispose toward worse COVID-19 outcomes. We conducted a retrospective cohort study to investigate the relationship of atopic dermatitis with COVID-19 symptom severity, hospitalization, length of hospital stay, requirement for oxygen therapy, long-term morbidity and mortality. Multivariable logistic regression models were constructed to examine the impact of atopic dermatitis (independent variable) on COVID-19 symptom severity, hospitalizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 6 publications
(11 reference statements)
2
6
0
Order By: Relevance
“…Previous studies showed no association of COVID-19related complications for adult AD. 3 This study's results suggest similar findings in pediatric AD patients because they demonstrated no higher risk of COVID-19-related complications. However, pediatric AD patients demonstrated a lower risk for 30-day hospitalization compared with matched non-AD children.…”
Section: Covid-19 Outcomes In Pediatric Patients With Atopic Dermatit...supporting
confidence: 77%
See 1 more Smart Citation
“…Previous studies showed no association of COVID-19related complications for adult AD. 3 This study's results suggest similar findings in pediatric AD patients because they demonstrated no higher risk of COVID-19-related complications. However, pediatric AD patients demonstrated a lower risk for 30-day hospitalization compared with matched non-AD children.…”
Section: Covid-19 Outcomes In Pediatric Patients With Atopic Dermatit...supporting
confidence: 77%
“…Research on COVID-19 outcomes in pediatric AD patients is sparse. Previous studies showed no association of COVID-19–related complications for adult AD 3 . This study's results suggest similar findings in pediatric AD patients because they demonstrated no higher risk of COVID-19–related complications.…”
supporting
confidence: 83%
“…However, AD has not been associated with increased COVID-19 severity or complications in other epidemiologic studies. 18 Asthma, which shares a similar immunologic profile to AD with IL-4 and IL-13-mediated airway inflammation, has also not been correlated with an increased risk of COVID-19 infection or severe disease. [19][20][21] Several hypotheses have been proposed to explain these findings, including the variable role of type 2 immune response in responding to SARS-CoV-2, as well as other physiological changes in asthma, asthma medications, and behavioral factors.…”
Section: Discussionmentioning
confidence: 99%
“…AD, a form of eczema, is an allergic skin disease often related to asthma, food allergy, allergic conjunctivitis, and AR 29 . In observational studies, the relationship between AD and COVID-19 remained murkier: some studies [30][31][32] suggested that AD was associated with increased risk for COVID-19, while others suggested that it was associated with reduced risk [33][34][35] or had no effect 36 . Cohort studies have shown a reduced risk of SARS-CoV-2 infection in patients with AD treated with Dupilumab 35 .…”
Section: Discussionmentioning
confidence: 99%